2005
DOI: 10.1063/1.2053354
|View full text |Cite
|
Sign up to set email alerts
|

Thermally-induced formation of Si wire array on an ultrathin (111) silicon-on-insulator substrate

Abstract: We have found that a Si wire array is formed by thermal agglomeration of an ultrathin (111) Si layer in a bonded silicon-on-insulator (SOI) structure, although previous studies for crystalline and amorphous Si layers on SiO2 only showed island formation. As starting material, (111) bonded SOI wafers with the top Si layers thinned to 5–9 nm were used. The samples were then subjected to a thermal treatment at 950 °C in an ultrahigh vacuum. Atomic force microscopy revealed that the (111) top Si layer is deformed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…Comparing the results in Fig. 1 and the previous results on (100) 2-6,10) and (111) SOI samples, 8,9) it was also obtained that the resultant agglomerated Si shape and direction are different for each crystal orientation SOI sample.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Comparing the results in Fig. 1 and the previous results on (100) 2-6,10) and (111) SOI samples, 8,9) it was also obtained that the resultant agglomerated Si shape and direction are different for each crystal orientation SOI sample.…”
Section: Resultssupporting
confidence: 68%
“…2(c)], {311} facets are also found on the Si wire sidewall, and it is suggested that the {311} facets determine the direction of Si wire in h112i directions. 8) Figure 3(a) shows a magnified AFM image of a typical Si island along the ½ 2 221 direction obtained from the (110) sample. It can be seen that the island is facetted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4,7,10 Void fingers have been observed to penetrate the thickened walls of these voids and preferentially grow into equivalent in-plane ͗310͘ directions. 7,28 This anisotropic dewetting behavior can be understood in terms of a small perturbation on the behavior that is predicted by the isotropic dewetting model we have presented here, caused by the anisotropic surface energies in Si. 10 The thickened void edges in these films have been found to break down and form void fingers in the three symmetrically equivalent in-plane ͗211͘-type directions.…”
Section: -6mentioning
confidence: 62%
“…10 The thickened void edges in these films have been found to break down and form void fingers in the three symmetrically equivalent in-plane ͗211͘-type directions. 28 However, an anisotropic version of the basic isotropic dewetting theory that we have presented here that fully predicts dewetting geometry and kinetics from a material's Wulff plot and anisotropic surface diffusivity tensor represents a major open theoretical problem. 7,28 This anisotropic dewetting behavior can be understood in terms of a small perturbation on the behavior that is predicted by the isotropic dewetting model we have presented here, caused by the anisotropic surface energies in Si.…”
Section: -6mentioning
confidence: 99%